Origins and the rise of Turkish nationalism: A case study: Türk Yurdu - Akın, Rıdvan, 1959- (Thesis (M.A.)-Bogazici University. Institute of Social Sciences, 1988., 1988)
As is well-known, Turkish Nationalism became the dominant ideology of the late constitutional period and continued to be so until the establishment of the Republic. As as ideology it initially confronted the other deeply rooted mentalities and their political forms, such as Ottomanism and Pan-Islamism. Howeyer, the pressing needs and decaying conditions of the Ottoman body politic which gave rise to Turkish Nationalism also brought it to the forefront of the circles of power. Leading Nationalists among the emigrant figures such as Akçuraoğlu, Ağaoğlu and the like from the North were thus able to find a positive atmosphere to disseminate their long held views as the immediate Natianalist aims. Other nationalists saw the First World War as the opportunity to break away from the restrictive conditions imposed by the imperial powers on the Ottomans for centuries. Despite the fact that The Empire in its struggle against the Entente powers gradually went through many phases ending up with the inevitably collapse by 1918, this did not mean the end of Turkism as an idealogy but its survival and resurgence in a wore rational and limited form in setting up of the new state; the Republic of Turkey.
Keywords: Nationalism -- Turkey -- History.